Pax genes in eye development and evolution - Kozmik, Zbynek (Current opinion in genetics & development, 2005)
Animal eyes with widely different anatomical designs have long been thought to arise independently, multiple times during evolution. This view was challenged about a decade ago by the landmark discoveries that Pax6, a highly conserved transcription factor, plays a key role in eye morphogenesis in both flies and mammals. Since then, more evidence has emerged in favour of the redeployment of Pax6 and some other developmental control genes within the genetic program underlying eye formation throughout the animal kingdom. Recent work has indicated that other members of the Pax gene family play a pivotal role in eye morphogenesis. The Eye gone gene regulates eye growth in Drosophila, whereas the PaxB gene is implicated in visual system development in jellyfish, the most basal organism possessing eyes.
Keywords: Animals; Morphogenesis; Repressor Proteins; represorové proteiny; Gene Expression Regulation, Developmental; modely genetické; morfogeneze; homeodoménové proteiny; Evolution, Molecular; molekulární evoluce; transkripční faktory paired box; Eye Proteins; Models, Genetic; oční proteiny; oči; Eye; Homeodomain Proteins; Paired Box Transcription Factors; transkripční faktor PAX6; PAX6 Transcription Factor; zvířata; vývojová regulace genové exprese